In the eyes of strays: stray cats awareness / Nur Hidayah Osman - Osman, Nur Hidayah (Faculty of Art and Design, 2020)
It's hard to believe that Malaysian have strays issue especially cruelty cases. Presents a new platform for stray cat awareness campaign among kids-thru digital comic strips.